Transforming Post-Divorce Alimony in Indonesian Religious Courts: A Maqashid al-Sharia Analysis - Kholid Saifullah; Syamsul Huda; Isnain La Harisi; Rizky Kurniawan (MASI Mandiri Edukasi, 2026)
Post-divorce alimony remains a significant issue in Indonesian religious courts because formal legal recognition does not always ensure substantive protection for divorced women. This article examines how post-divorce alimony is determined in Indonesian religious courts and evaluates whether recent judicial reasoning remains consistent with maqashid al-sharia. The study focuses on Decision No. 291/Pdt.G/2021/MS.Str and compares it with two other religious court decisions. Using a normative juridical method, it combines statutory, case, and conceptual approaches. The analysis applies maqashid al-sharia, particularly hifzh al-nafs, hifzh al-mal, and hifzh al-nasl, as the main evaluative framework. The findings show that the principal decision relied heavily on mediation outcomes and awarded iddah maintenance of IDR 3,000,000 without an independent proportionality assessment. It also failed to explicitly award mut’ah despite a 39-year marriage and the existence of ten children. These findings indicate a shift from a normative-textual approach toward a pragmatic-mediative model. The article contributes theoretically by demonstrating the application of maqashid al-sharia in evaluating judicial reasoning. It highlights the policy need for stronger gender-sensitive adjudication, closer scrutiny of mediated settlements, and adaptive guidelines for post-divorce alimony in Indonesian religious courts.